2012
DOI: 10.1016/j.ausmj.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Personal Values and Mall Shopping Behavior: The Mediating Role of Attitude and Intention among Chinese and Thai Consumers

Abstract: Personal values are important determinants of consumer behavior. While previous research has identified values (i.e., openness to change and self-enhancement) which guide consumers’ mall shopping behavior, they have been set in a Western cultural context. By adopting a value–attitude–behavior (VAB) model, this study examines what and how personal values influence consumers’ mall shopping behavior in two non-Western countries, namely China and Thailand. The results confirm the existence of the causal flow of VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 91 publications
(147 reference statements)
3
51
0
1
Order By: Relevance
“…Prior research illustrates the motivating factors for shopping and found reasons other than the need for products and services (Tauber, ; Babin et al ., ; Babin and Darden, ; Arnold and Raynolds, , ; Haans and Gijsbrechts, ; Cai and Shannon, ). However, results are mixed and most studies have been conducted in developed country contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research illustrates the motivating factors for shopping and found reasons other than the need for products and services (Tauber, ; Babin et al ., ; Babin and Darden, ; Arnold and Raynolds, , ; Haans and Gijsbrechts, ; Cai and Shannon, ). However, results are mixed and most studies have been conducted in developed country contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The values of an individual have an effect on their behavior as consumers through their attitudes, which in turn impact on their choices within the value exchange [1,10,17,23]. Additionally, it has been shown that values relate to real-life choice, and may also influence behavior through different manifestations, such as habits [18].…”
Section: Contributionmentioning
confidence: 97%
“…Ulusla rarası literatürde, AVM'lerin farklı yönlerini ele alan pekçok çalışmanın (Cai & Shannon, 2012-Azhari vd., 2012-Jackson vd., 2011-Allard vd., 2009-Yuan & Krishna, 2008-Wesley vd., 2006-Chebat vd., 2005-Coughlan & Soberman, 2005-Swinyard, 1998-Goss, 1993) yapıldığı görülmektedir. Ülkemizde AVM'lere yönelik yapılmış bazı alan araştırmaları ve bulgular tablo 1'de özetlenmektedir.…”
Section: Alışveriş Merkezlerinin Tercih Nedenleri Ve Yapılan Araştırmunclassified